Community Development for Elderly Health Promotion in Samut Prakan Province - Wongprasert, Prakit (Journal of Preventive Medicine Association of Thailand, 2023)
Objective: The objectives are to 1) study the situation and health conditions of the elderly in Samut Prakan Province 2) evaluate the community’s participation in promoting the health of the elderly in Samut Prakan Province 3) develop the potential of the community to carry out health promotion for the elderly people in Samut Prakan Province effectively and 4) to evaluate development results and draw lessons from community capacity development in promoting the health of the elderly of Samut Prakan Province. Methods: This research design is mixed method research consisting of quantitative research and action research. Sample groups used in quantitative research include all citizens aged 60 years and over who live in the Samut Prakan Province area and come to receive medical and public health services at the Public Health Service Unit in the Samut Prakan Province area. Operational research including the Subdistrict Health Fund Committee, community leaders, and people involved in the development process of the study areas, totaling 3 communities, including communities in urban areas, semi-urban area and rural areas, each community has 60 people, totaling 180 people. Quantitative tools include data recording forms, data assessment forms and Qualitative survey include Situation assessment form and group discussion (Focus Group) Results: The results of the research found that 1) Most of the elderly in Samut Prakan Province are in the early elderly group (age 60-69 years), more than 50 percent, most of them live in urban areas. 77.51 percent have been screened for health in Fiscal year 2021, 53.21 percent found 35.78 percent of elderly people with at-risk conditions. 2) Community participation, Most participation is low participation 3) Developing the potential of the community to be able to participate in promoting the health of the elderly. in the area, both in terms of knowledge about operations in promoting health of the elderly and the preparation of community plans and putting the plan into practice will make operations more efficient and 4) From the meeting of the working group, the researchers agreed that the learning process in the form used as well as the direction and operation by those who are involved or have stakeholders in the area. Conclusion: The process of developing the potential of those involved is very important and necessary. It will allow those involved to see the benefits of developing together will make the development process more efficient and most importantly, everyone wants their own community to be a community that can be self-reliant and have sustainable development.